Production Du Bili-Bili, Biere Traditionnelle De Sorgho Du Nord Cameroun : Diversité Des Procédés De Production Et Qualité Des Produits - Charles, Touwang; Jong, Nso Emmanuel; Robert, Ndjouenkeu (European Scientific Journal, ESJ, 2018)
The production of "bili-bili", a fermented drink made from sorghum, is one of the main components of urban food craft structures in North Cameroon. The technical practices incorporate differentiations justified by the adaptation of local technical availabilities thus leading to a variability of the final product quality. This study was therefore conducted in order to determine the influence of the various local practices identified in this part of Cameroon on intermediate products and the finished product. This study shows that the raw material (djigari) has a good malting ability with a weight of thousand grains of 29.57g, a germinative energy and a germinative capacity of 96 and 93.75% respectively. Its protein content is 12.79% and the total tannin and polyphenol contents are 0.47 and 0.64% respectively. The physicochemical parameters of samples taken at different stages of production vary by process. The different processes have a significant effect (P ˂0.05) on the physicochemical characteristics of "bili-bili" with the exception of the alcohol content. The ACP plane projection of the relations between the "bilibili" characteristics and the different processes has shown that the four beers produced from the different processes are all different.